2005
DOI: 10.1007/s00395-005-0556-1
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte colony–stimulating factor–induced blood stem cell mobilisation in patients with chronic heart failure

Abstract: Bone marrow-derived stem cells may contribute to the regeneration of non-haematopoietic organs. In order to test whether an increase in circulating stem cell numbers improves impaired myocardial function we treated 16 male patients with chronic heart failure due to dilated (DCM; n = 7) or ischaemic cardiomyopathy (ICM; n = 9) with the stem cell mobilising cytokine granulocyte colony-stimulating factor (G-CSF; four 10-day treatment periods interrupted by treatment-free intervals of equal length). Safety and eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 30 publications
1
26
1
Order By: Relevance
“…GGT levels usually increase in ischemic stroke [16] while bilirubin level only decreases 10 days after onset [17]. It is also known that G-CSF increases GGT but not bilirubin levels in patients with chronic heart failure [18]. With regards to GGT, our findings might have been accidental, as the difference between the groups was recorded only once.…”
Section: Discussioncontrasting
confidence: 47%
“…GGT levels usually increase in ischemic stroke [16] while bilirubin level only decreases 10 days after onset [17]. It is also known that G-CSF increases GGT but not bilirubin levels in patients with chronic heart failure [18]. With regards to GGT, our findings might have been accidental, as the difference between the groups was recorded only once.…”
Section: Discussioncontrasting
confidence: 47%
“…Furthermore, enhanced sympathetic reinervation and higher levels of noradrenaline, which increased the incidence of ventricular arrhythmia episodes after electrical stimulation, were observed [64]. Huttmann et al [65] described that patients with heart failure who received G-CSF showed an increased risk of angina or ventricular arrhythmias. Therefore, the safety of G-CSF in other clinical conditions needs to be evaluated.…”
Section: Electrophysiological Propertiesmentioning
confidence: 97%
“…However, the FIRSTLINE-AMI [85] and STEMMI trials [86] reported a restenosis rate within the expected range. This was partly due to a different and more strict selection of patients, in the latter studies, regarding age, severity of coronary artery disease, chronicity of myocardial infarction and onset of subcutaneous G-CSF delivery after PCI of the IRA [90][91][92][93] ( Table 5). Orlic et al [25] G-CSF and SCF Mice Improved cardiac function and hemodynamics, decrease in infarct size Kocher et al [74] Recombinant Human G-CSF Rat Improved neoangiogenesis in the infarcted region, prevention of ventricular remodeling Minatoguchi et al [75] G-CSF Rabbit Accelerated absorption of necrotic tissue, enhanced myocardial regeneration, improved cardiac function Harada et al [76] G-CSF Mice Improved cardiac function, direct effect on survival, apoptosis and function of cardiomyocytes Sugano et al [77] G-CSF Rat Improvement of cardiac function and accelerated healing of the infarcted tissue.…”
Section: Mobilization Of Stem/progenitor Cellsmentioning
confidence: 98%